Impact of slow transit constipation on the outcome of laparoscopic ventral rectopexy for obstructed defaecation associated with high grade internal rectal prolapse. (December 2013) - Gosselink, M. P.; Adusumilli, S.; Harmston, C.; Wijffels, N. A.; Jones, O. M.; Cunningham, C.; Lindsey, I.
Abstract Aim Limited literature exists on whether slow colonic transit adversely influences the results of outlet obstruction surgery. We compared the functional results of laparoscopic ventral rectopexy (LVR) for obstructed defaecation secondary to high grade internal rectal prolapse in patients with normal and slow colonic transit. Method Consecutive patients suffering from obstructed defaecation associated with an internal rectal prolapse, who underwent an LVR between 2007 and 2011, were identified from a prospective database. All patients underwent preoperative defaecating proctography, anorectal manometry and colonic transit studies. Symptoms were assessed preoperatively and at 12 months after operation using a standardized questionnaire incorporating the Patient Assessment of Constipation Symptoms (PAC‐SYM) questionnaire, the Fecal Incontinence Severity Index (FISI), the Patient Assessment of Constipation Quality of Life (PAC‐QOL) scale and the Gastrointestinal Quality of Life Index (GIQLI). Results In all, 151 patients underwent LVR, 109 with normal and 42 with slow colonic transit. Preoperatively there was no significant difference between the two groups in age, sex, PAC‐SYM score or FISI score. The PAC‐SYM and FISI scores were significantly reduced in both groups at 12 months (P < 0.001). When comparing the change from baseline of PAC‐SYM between patients with and without slow transit constipation, a significant difference was observed (P = 0.030) with changes of 58% and 40%. Quality of life (GIQLI and PAC‐QOL) was equally improved in both groups. Quality of life improvement was less in patients with right colonic stasis. Conclusion Slow colonic transit has no adverse impact on function and quality of life after LVR for obstructed defaecation due to high grade internal rectal prolapse.